Er2O3 doped zinc borosilicate glass substrate: Impact of doping to the structural, optical and surface plasmon resonance performance - Al-Nidawi, Ali Jabbar Abed; Matori, Khamirul Amin; Zaid, Mohd Hafiz Mohd; Chyi, Josephine Liew Ying; Tee, Tan Sin; Khushaini, Muhammad Asif Ahmad; Zain, Ahmad Rifqi Md; Mutlage, Wurood Rahi; Abuallan, Mohammad Ayman; Efa, Abdelkader Mohammed (Springer Science and Business Media, 2024)
The optimization of glass substrate optical properties for enhanced biosensor sensitivity has recently blossomed into a major research focus, yielding remarkable progress. Nevertheless, attaining precise control over nanoscale morphologies and their light-altering abilities remains a formidable hurdle, necessitating the exploration of diverse strategies to overcome this issue. This study was conducted to investigate how Er2O3 doping affects the physical, optical structural and elastic properties of ZnO-SiO2-B2O3 glasses, which were created using the melt-quenching method. The samples were confirmed to be amorphous and glassy using XRD and FTIR techniques. Many researchers used ultrasonic waves to measure the longitudinal and shear velocities of glasses using the pulse-echo method. The measurements were taken at a temperature within the typical room range and a frequency of 5 MHz. The addition of Er2O3 as a dopant resulted in both decreasing and increasing trends in the longitudinal, Young, shear and bulk moduli. These observations suggest a potential correlation between the increase in acoustic impedance and the presence of bridging oxygen, which leads to stiffer and more compact glass structures. The optical band gap of the material decreased from 3.43 eV to 3.23 eV as the weight percentage of Er2O3 increased from 0.00 to 0.05 wt.%. Surface plasmon resonance was investigated using the Otto configuration. The observed wavelength shift, approximately 6 nm with a gold nanolayer coating in the SPR results, indicated an increase in wavelength with increasing Er2O3 content (0.01-0.05 wt.%). This highlights the potential of this glass substrate for various optical applications, including optical biosensors.